WT1 protein is cleaved by caspase-3 in apoptotic leukemic cells. Issue 1 (2nd January 2018) - Ruan, Jichen; Gao, Shenmeng; Yang, Junjun; Li, Haiying; Huang, He; Zheng, Xiaoqun
Abstract: The aberrant overexpression of Wilms' tumor-1 gene ( WT1 ) plays an important role in blast cell survival and resistance to chemotherapy in acute myeloid leukemia (AML). Here, we found in chemotherapeutic drug etoposide-induced apoptosis, WT1 protein was cleaved into smaller fragment by caspase-3 in leukemic cells. The cleavage was blocked by pan-caspase inhibitor and special caspase-3 inhibitor, suggesting that caspase-3 might cleave WT1 protein. Furthermore, recombinant active caspase-3 cleaved the Flag-WT1 and GST-WT1 proteins in vitro . However, site-directed mutagenesis analyses failed to identify caspase-3-targeted sites in WT1 protein, indicating that caspase-3 cleaved uncommon sites but not classical motifs (DXXD) and non-classical motifs (XXXD). Finally, Eto decreased c-Myc and Bcl-2 expression via reducing the binding of WT1 to the promoter and Eto-induced apoptosis was partially prevented by overexpression of WT1. Collectively, we identify a new substrate for caspase-3 and shed new light on understanding the complicated biology of WT1 in leukemia.